(untitled) (International Journal of Current Engineering and Technology, 2015)
A number of variety of centrifugal pump have been constructed and used in many different applications in domestics, Agricultural, industry and other technical sectors. Due to the great number of free geometric parameters, their design and performance prediction process is still a difficult task, mainly the effect of which cannot be directly evaluated. The significant cost and time of the trial-and-error process by constructing and testing physical prototypes is always undesirable. For this reason taking one analysis parameter, design the pump result check by software and finally check the result by experimental method. Analysis is currently being used in the design and construction stage of various pump types, the use of which reduces significantly the new pump development time and costs. The numerical simulation can provide quite accurate information on the fluid behavior in the machine, and thus helps the engineer to obtain a thorough performance evaluation of a particular design. Performance study predicts the performance of pump impellers and helps us rapidly to establish the efficiency of the pump over various operating conditions.